PELATIHAN DAN PENDAMPINGAN PEMBUATAN LAPORAN KEUANGAN SEDERHANA SESUAI STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH (SAK EMKM) DI WARKOP TETANGGA - Baskoro, Fandi; Efendi, Kamila Kalsum; Ramadhana, Nur Anisah; Septiyani, Herma; Keban, Agustina Hira; Rahmadi, Zara Tania; Dharma, Dias Adi (ASOSIASI IDEBAHASA KEPRI, 2024)
The UMKM sectors serves as a driving force in the economy, contributing to the welfare of economy players, one of which involves creating simply finansial reports to asses whether a business is making a profit or expressing losses. The purpose of a study is to provide training to enterpreneurs in maintaining and creating simply finansial records over one month period. The method employe is comunity engagement conducted at Warkop Tetangga, Jalan Pitara, Pancoran Mas Depok. The research findings indicate that enterpreneurs have begun implementing simply finansial reports by recording daily income and expenses, serving as motivation for them to continue generating finansial reports on a monthly basis.